The valuation effect and determinants of corporate contracting : a thesis presented in partial fulfillment of the requirements for a Master of Business Studies at Massey University, December 2002 - Chen, Lijia (Massey University, 2002)
This study examined abnormal stock market returns to equity holders around corporate contract announcement that were obtained from Dow Jones & Company, Inc. between January 1, 1990 and December 31, 2000. Of the 7137 contract announcement found, 984 contract winning companies (contractee) and 575 contract giving companies (contractor) were not contaminated by other announcements and have sufficient CRSP data to enter the final sample that was analyzed for excess returns to the contractees. Excess returns were also analyzed for the contractors. The Asymmettic Information Hypothesis and Information Content Hypothesis were used to develop hypotheses that predict contract announcement abnormal returns. The Market Model was used to analyze abnormal returns for both the contractees and contractors. As expected, statistically significant cumulative average excess returns were found for contractee companies, but not for contractor companies. Contractee excess returns were also examined for different industry groups. Also, the international or domestic nature of the contractor is analyzed for differences in abnormal returns. Contrary to expectations, the market reacted with more significant abnormal return for domestic contracting than the international contracting. Finally, cross-sectional regression models are developed to test the statistical significance of variables relative to sample characteristic, firm size, profitability, and information asymmetries of firm. Contractee relative contract size was found to have significant impact on cumulative average abnormal returns. Dummy variables were included in the cross-section model to account for the sequence of the contract and nationality of the contractee and contractor, but they were statistically insignificant to the model. The variables for contractor's firm were also statistically insignificant in effecting abnormal returns for their equity.
Keywords: Corporations -- Valuation; Public contracts